INVESTIGATING PROJECT-BASED VLOG TO IMPROVE STUDENTS’ SPEAKING SKILL IN REAL WORLD ACTIVITY - Zubaidi, Zubaidi; Suharto, Ririn Pratiwi (NextGen Education Review Journal, 2024)
Monotonous speaking practice is carried out in classroom. This activity is only carried out by two-way communication between lecturers and students. It becomes problematic for students to practice speaking. To overcome this problem, it is necessary to innovate speaking learning models by utilizing technology. Vlog can be used as technology tool for speaking. The aim of this research is to identify the success of implementing project-based vlogs to improve students’ speaking skills. This research uses a combination research method, namely quantitative and qualitative. The research instrument uses observation sheets and pre-test and post-test scores. The research results show that the application of project-based learning with technology has succeeded in improving students’ speaking skills through creating students’ vlogs. The students’ speaking skill improved in the aspects of pronunciation, grammar, vocabulary, fluency and understanding. The research results can be concluded that project-based learning is very suitable to be implemented at the Politeknik Negeri Malang because it is in accordance with the objectives of providing vocational education. Based on these findings, students’ English vlogs can be used as learning models in speaking class.